'He Saw Heaven Opened': Heavenly Temple and Universal Mission in Luke-Acts. (January 2022) - Moore, Nicholas J.
Abstract: Numerous scholars have argued that in Luke-Acts the location of sacred space or divine presence passes from the Jerusalem temple to Jesus, Christian believers, or both; in Acts, this transfer is understood as integral to the universal mission. The present article argues that such studies overlook the important motif of heaven as temple, which plays a role in Jesus' trial and crucifixion and the Stephen and Cornelius episodes. Using Edward Soja's spatial theory, previous studies' binary categorisation of temple space is critiqued. The heavenly temple disrupts and reconstitutes understandings of sacred space, and thus undergirds the universal spread of the Way.